Intracellular recordings from myenteric neurones in the human colon. - Brookes, S J (1987)
1. Intracellular recordings were made from cells in the myenteric plexus of the human colon in freshly dissected tissue obtained from patients undergoing surgery for the removal of carcinomas or diverticular bowel. 2. Twenty-seven cells from ten preparations were classified as neurones and had overshooting action potentials, an average resting potential of -54 +/- 9 mV, an average input impedance of 1.05 +/- 0.59 x 10(8) omega and a variety of synaptic inputs. 3. Twenty-three (out of twenty-five neurones tested) received nicotinic fast excitatory synaptic inputs (fast e.p.s.p.s) that were blocked reversibly by hexamethonium and mimicked by acetylcholine. These nerve cells bore a close resemblance to S cells that have been characterized in the guinea-pig small-bowel myenteric plexus. 4. One cell had a long after-hyperpolarization following its impulses and was similar to AH cells in the guinea-pig small bowel. 5. Three neurones received inhibitory synaptic inputs, up to 15 mV in amplitude, lasting up to 10 s, associated with a decrease in input impedance and with a reversal potential between -80 and -90 mV. 6. Slow excitatory synaptic potentials were only detected in the single AH cell. The slow e.p.s.p. was associated with a depolarization of up to 12 mV, an increase in excitability and an increase in the input impedance of the neurone. 7. The proportion of S and AH cells differ considerably from that reported in the guinea-pig small-bowel preparation. Possible causes of the differences are discussed.